Development of Islamic Religious Education Curriculum And Its Implementation at MTs Al Khoziny Buduran Sidoarjo - Su'eb, Su'eb (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
The research aims to: describe the implementation of the PAI curriculum in the subject of Aqidah Akhlaq. This research method uses qualitative research. The research data was obtained from the results of recording from Aqidah Akhlaq teachers in implementing the PAI curriculum. The data analysis techniques used are classifying, combining, interpreting, and inferring. The results of the research on the development of the PAI curriculum: 1) Centered on the potential development, needs, and interests of students and their environment, 2) Diverse and integrated, 3) Responsive to the development of science, technology, and art, 4) Relevant to the needs of life, 5) Comprehensive and sustainable, 6) Lifelong learning, 7) Balanced between national interests and regional interests. Implementation at MTs Al Khoziny Buduran Sidoarjo, namely: 1) Holding a Workshop or socializing about making lesson plans, 2) Using package books from the Ministry of Religion and also pesantren books (Yellow Book), and 3) In learning PAI Aqidah Akhlaq on three aspects of cognitive, affective, and psychomotor. This article has a scientific contribution in curriculum development and implementation, especially for the Islamic Religious Education curriculum that is effective for schools in Islamic boarding schools in Indonesia.